The Rise in Household Liquidity - La Cava, Gianni; Wang, Lydia (My University, 2021)
It is well documented that household wealth has risen significantly in recent decades and that both sides of the household balance sheet – assets and liabilities – have expanded. We document a less well-known phenomenon: household liquid assets (such as cash, deposits and equities) have also risen strongly relative to income over the same period. This is true for Australia and for most advanced economies. We explore the determinants of liquidity across households and over time, using a range of household surveys for Australia. We find that household liquidity is strongly associated with life cycle factors, such as age and housing tenure. The increase in liquidity over recent decades has been broad based across households, though strongest amongst those with mortgage debt. Consistent with this, the share of liquidity-constrained households has declined significantly. The growth in liquidity is closely connected to developments in the housing market. First, higher housing prices have lifted the deposit requirement for potential home buyers, encouraging such households to save more in liquid assets. Second, higher mortgage debt has increased the repayment risks associated with future income declines, leading indebted home owners to save more for precautionary reasons, partly through paying down debt ahead of schedule. The process of building wealth and liquidity through debt amortisation has been supported by the trend decline in interest rates and unique financial innovations such as mortgage offset and redraw accounts that have made housing wealth more liquid. Overall, the rise in household liquidity appears to have increased the financial resilience of the household sector.
Research Discussion Paper Series
Keywords: Housing, communities and neighbourhoods; Income, wealth and finances